Inhibition of LINC01048 decreases cell proliferation and induces the apoptosis in gastric cancer - Jinxi Huang; Weiwei Yuan; Gaofeng Li; Beibei Chen; Lihong Wang; Yulong Chen; Hai Huang (Discover Oncology)
Abstract With advancements in the study of long non-coding RNAs (lncRNAs) as significant biomarkers and therapeutic targets in various human diseases, including cancer, neurodegenerative conditions, and genetic disorders, emerging evidence highlights their regulatory roles in the development of gastric cancer (GC). However, the mechanisms underlying these functions remain largely unknown. In this study, we investigate the role of the LINC01048 in tumorigenesis and cell proliferation in GC cell lines, such as HGC27 and MKN45. Analysis of publicly available databases and experimental validation revealed that LINC01048 expression is elevated in GC tissues and cell lines and is associated with poor prognosis. Knockdown of LINC01048 significantly suppressed cell proliferation and induced apoptosis in GC cells. Additionally, depletion of LINC01048 reduced the nuclear localization of β-catenin while increasing its cytoplasmic retention. Furthermore, treatment with SKL2001, a Wnt/β-catenin pathway activator, reversed the effects of LINC01048 knockdown on cell proliferation and apoptosis. In vivo experiments confirmed that LINC01048 depletion decreased tumor growth in GC xenograft models. Overall, these findings suggest that LINC01048 plays an oncogenic role in GC by promoting cell proliferation and modulating the Wnt/β-catenin pathway. Therefore, LINC01048 may serve as a potential therapeutic target for GC treatment.